PERLINDUNGAN HUKUM TERHADAP EFEK SYARI’AH DALAM HUKUM PASAR MODAL DI INDONESIA - Fahrunnisa Fahrunnisa; Bismar Nasution; Mahmul Siregar (TRANSPARENCY, 2019)
Capital market is a market in the abstract sense that brings prospective investors (investors) with issuers (companies that issue securities in the capital market) that require long-term funds, which is regulated by Law No. 8 of 1995 on capital markets, but how the related arrangements The effect of syari'ah which in this era of globalization is increasingly interested in considering the syari'ah capital market is becoming alterative in collecting funds and as an investment opportunity syari'ah free from the elements of usury, gharar and mayshir. And how the effect of syari'ah in the perspective of the capital market law. The type of research used in the writing of this thesis is normative juridical research by collecting data in library research along with collecting legislation related to capital market activity and similar implementing regulation related to syari'ah capital market. Sources of data in this study are primary legal materials, secondary legal materials, tertiary and all three data are analyzed qualitatively. Based on the results of this study can be concluded that the effect of shari'ah in the law of capital markets in Indonesia that gives assertion that all activities based on syari'ah then must be in accordance with the principles of syari'ah. And with this required role by the National Syari'ah Council (DSN-MUI) as the supervisor of the principles of syari'ah in determining the criteria of syari'ah. However, the DSN-MUI fatwa is considered non-binding because of the absence of DSN MUI into the legislative regulation of the Republic of Indonesia, and demands a sharia stock exchange purely from the principles, mechanisms of issuance and trade transactions based on Islamic law